An unusual new species of Gyrinidae (Coleoptera), Orectochilus orbisonorum n. sp., from India - Miller, Kelly B.; Mazzoldi, Paolo; Wheeler, Quentin D. (Zootaxa, 2008)
A new species of Gyrinidae, Orectochilus orbisonorum n. sp., is described to honor the late Roy Orbison, recording artist and songwriter, and his wife Barbara. The species is unique among Indian Gyrinidae and Orectochilus Lacordaire, in general, since the ventral surfaces are white as the result of clear areas of cuticle allowing internal tissues to be visible.